Quercetin ameliorates obesity and inflammation via microbial metabolite indole-3-propionic acid in high fat diet-induced obese mice - Lu, Jiaxin; Huang, Yanting; Zhang, Yujing; Xie, Jiayu; Guo, Qingjun; Yang, Huifan; Yang, Yunyan; Chen, Jing; Su, Lijie (Frontiers in Nutrition, 2025)
BackgroundObesity is a chronic metabolic disease, mainly caused by excessive/abnormal fat accumulation, as well as accompanied by endotoxemia and chronic inflammation. Quercetin, a natural flavonoid, may alleviate obesity by regulating gut microbiota and metabolites, but its exact mechanism for improving obesity is unknown.ObjectivesThe aim of this study was to investigate the effects of quercetin on high-fat diet (HFD)-induced obesity in mice. In particular, we focused on the regulatory effects of quercetin on gut microbiota and the tryptophan metabolite indole-3-propionic acid (IPA).MethodsThe C57BL/6J mice were subjected to a 20-week HFD feeding regimen with concurrent daily oral administration of quercetin or IPA. The body weight, fat accumulation, gut barrier function, and chronic inflammation were determined. Gut microbiota composition was analyzed by 16S rRNA sequencing and IPA levels were measured in serum and feces. In vitro experiments, Caco-2 cells were used to evaluate the effects of IPA and fecal dilutions from quercetin-treated mice on tight junction protein expression and aryl hydrocarbon receptor (AhR) activation.ResultsOur results revealed that quercetin supplementation significantly mitigated obesity and chronic inflammation, and improved the disrupted gut barrier function through the actvation of AhR/interleukin 22 (IL-22) pathway. 16S rRNA sequencing revealed that quercetin treatment increased the abundance of Lactobacillus. Quercetin intervention increased the levels of IPA in the serum and feces of mice. IPA supplementation alleviated obesity and chronic inflammation, and enhanced intestinal barrier function through AhR activation. The findings were further corroborated by Caco-2 cell experiment, which indicated that the modulation of the dysregulated gut microbiota to change microbial metabolite IPA coordinated the improvement effect of quercetin on gut barrier disruption.ConclusionQuercetin supplementation alleviates obesity by restoring high-fat diet induced gut microbiota disorder, which elevates IPA level to activate AhR/IL-22 pathway, thereby enhancing intestinal barrier integrity and suppressing chronic inflammation.